A case of an unjustified Aphid name emendation - Entiauspe-Neto, Omar M.; Abegg, Arthur Diesel (Zootaxa, 2019)
The norms regarding validity and formulation of specific epithets in Zoology are ruled by the International Code of Zoological Nomenclature (ICZN 1999), a published convention of the International Commission on Zoological Nomenclature, that operates under a vast array of underlying nomenclatural principles. One of its components is Article 31, which rules upon the formation of specific or subspecific epithets for personal names, by the use of nomina (sensu Dubois 2007) under genitive case. As discussed by Dubois (2007), this has erroneously led several authors to assume that the aforementioned nomina should exclusively end in “-i” if dedicated to a man (or -orum, for plural), and in “-ae” if dedicated to a woman (or -arum, for plural) (being also important to state that this provision is sensitive on whether the chosen nomina is a modern personal name (Art. 31.1.2) or not (Art. 31.1.1)), leading to several independent proposed emendations to these names, which authors have considered as “wrong”, under the Code; the author then, proceeds to conduce a careful and extensive literature review on matter, proposing an amendment to the Code, correcting several unjustified emends, and highlighting that “[...] the stem of such a nomen is determined by the action of the original author when forming the genitive, and should be preserved by subsequent authors. Any subsequent demonstrably intentional change in the stem or ending of this nomen, other than correction of an inadvertent spelling error, must be considered an unjustified emendation [...]” (Dubois 2007: 64).